Differences in the chromatic visual event related potentials in number and non-number plates of the ishihara colour vision test - Mohammed , Almarri Faraj (2017)
Event-related potentials (ERPs) are very small voltages existed within the brain structures in response to particular events or stimuli. Ishihara colour vision test is a test that made of a number of coloured plates that might be either number plates or non- number plates. In a recent study, we looked for the differences of chromatic visual ERPs in number and non-number plates during visual presentation session in trichromatic participants to discover furthermore about which plate design can elicit more cognitive processes like attention and memory wherein these differences might be used as a new clinical knowledge, which might be applicable clinically in the future. A total of 25 participants both males and females were used for our study. All of them were apparently healthy with normal colour vision. Firstly, we recorded the electroencephalography (EEG) when participants attended to the lab in the Hospital of Universiti Sains Malaysia (HUSM) from 19 electrode sites using 128 electrode sensors net which were applied on the participant’s scalp according to 10-20 international electrode placement system. Then, we recorded ERPs through presenting a visual oddball task of number and non-number plates in a random order at inter-stimulus intervals (ISI) of 2 seconds.The latency and amplitude of the evoked N100, N200, P200 and P300 components were identified. To determine the statistical significance, the amplitude and latency of all components and the reaction time (RT) was analysed by using paired-t test. The results showed higher amplitudes of N100, P200 and N200 ERP components for number plates indicating that the participants had greater visual selective attention, visual searching perception and visual identification for number plates as compared to non- number. The results of longer latencies of N200 and P300 ERP components and the higher amplitude of P300 for non-number plates signifying that the participants were taking more time to identify and distinct visually the non- number plates and delaying in cognitive processing and attention for non- number plates as compared to number plates. About RT, the results showed significant increasing in mean of the non- number plates as compared with number plates indicating that the participants responded to number plates faster than non- number plates.Therefore, we concluded that besides colour vision tests, in research fields, the plates of Ishihara colour vision test could be potentially used in studies that deal with cognition, attention and memory which has been evidenced through the differences of the latencies and amplitudes of N100, P200, N200 and P300 ERP components in number and non-number plates viewing in our study. The findings of this study might be translatable clinically in patients with neuropsychological and attention disorders to discover new findings that might give benefits to the patients, medical researchers and clinicians in the future.